Do Owners Have a Clever Hans Effect on Dogs? Results of a Pointing Study - Schmidjell, Teresa; Range, Friederike; Huber, Ludwig; Virányi, Zsófia (Frontiers in Psychology, 2012)
Dogs are exceptionally successful at interpreting human pointing gestures to locate food hidden in one of two containers. However, it has repeatedly been questioned whether dogs rely on the pointing gesture or their success is increased by subtle cues from their human handler. In two experiments we used a standard two-way object-choice task to focus on this potential Clever Hans effect. We investigated if and how owners’ knowledge and beliefs influenced their dogs’ performance. In two experiments, as is typical in such pointing tasks, the owners sat behind their dogs, in close auditory and tactile contact with them. In Experiment 1, we systematically manipulated the owners’ knowledge of whether or not their dog should follow the pointing gesture, but at the same time instructed the owners to refrain from influencing the choice of their dog. We found no influence of subtle cues from the owners, if indeed they existed: dogs in the different groups followed the pointing uniformly. Furthermore, in the absence of pointing dogs chose randomly, even though the owners had been informed about the location of the reward. In Experiment 2, owners were instructed to actively influence the choice of their dogs, and they, indeed, succeeded in sending their dogs to the container they believed to be baited. However, their influence was significantly weaker if the experimenter had previously pointed to the other location. Overall the pointing gesture seems to have a strong effect on the choice of dogs in an object-choice task. Pointing can lead the dogs to success without help from their owners as well as it can counteract clear directional instructions provided by the owners.